A new generation of companion diagnostics: cobas BRAF, KRAS and EGFR mutation detection tests. (June 2014) - Angulo, Barbara; Lopez-Rios, Fernando; Gonzalez, David
Abstract : The cobas ® (Roche) portfolio of companion diagnostics in oncology currently has three assays CE-marked for in vitro diagnostics. Two of these ( EGFR and BRAF ) are also US FDA-approved. These assays detect clinically relevant mutations that are correlated with response ( BRAF, EGFR ) or lack of response ( KRAS ) to targeted therapies such as selective mutant BRAF inhibitors in malignant melanoma, tyrosine kinases inhibitor in non-small cell lung cancer and anti-EGFR monoclonal antibodies in colorectal cancer, respectively. All these assays are run on a single platform using DNA extracted from a single 5 µm section of a formalin-fixed paraffin-embedded tissue block. The assays provide an 'end-to-end' solution from extraction of DNA to automated analysis and report on the cobas z 480. The cobas tests have shown robust and reproducible performance, with high sensitivity and specificity and low limit of detection, making them suitable as companion diagnostics for clinical use.